Efficacy of treating pain to reduce behavioural disturbances in residents of nursing homes with dementia: cluster randomised clinical trial. (17th July 2011) - Husebo, Bettina S; Ballard, Clive; Sandvik, Reidun; Nilsen, Odd Bjarte; Aarsland, Dag
Abstract : Objective To determine whether a systematic approach to the treatment of pain can reduce agitation in people with moderate to severe dementia living in nursing homes. Design Cluster randomised controlled trial. Setting 60 clusters (single independent nursing home units) in 18 nursing homes within five municipalities of western Norway. Participants 352 residents with moderate to severe dementia and clinically significant behavioural disturbances randomised to a stepwise protocol for the treatment of pain for eight weeks with additional follow-up four weeks after the end of treatment (33 clusters; n=175) or to usual treatment (control, 27 clusters; n=177). Intervention Participants in the intervention group received individual daily treatment of pain for eight weeks according to the stepwise protocol, with paracetamol (acetaminophen), morphine, buprenorphine transdermal patch, or pregabaline. The control group received usual treatment and care. Main outcome measures Primary outcome measure was agitation (scores on Cohen-Mansfield agitation inventory). Secondary outcome measures were aggression (scores on neuropsychiatric inventory-nursing home version), pain (scores on mobilisation-observation-behaviour-intensity-dementia-2), activities of daily living, and cognition (mini-mental state examination). Results Agitation was significantly reduced in the intervention group compared with control group after eight weeks (repeated measures analysis of covariance adjusting for baseline score, P<0.001): the average reduction in scores for agitation was 17% (treatment effect estimate −7.0, 95% confidence interval −3.7 to −10.3). Treatment of pain was also significantly beneficial for the overall severity of neuropsychiatric symptoms (−9.0, −5.5 to −12.6) and pain (−1.3, −0.8 to −1.7), but the groups did not differ significantly for activities of daily living or cognition. Conclusion A systematic approach to the management of pain significantly reduced agitation in residents of nursing homes with moderate to severe dementia. Effective management of pain can play an important part in the treatment of agitation and could reduce the number of unnecessary prescriptions for psychotropic drugs in this population. Trial registration ClinicalTrials.gov NCT01021696 and Norwegian Medicines Agency EudraCTnr 2008-007490-20.